Experimental investigation of two-phase flow characteristics of nitrogen-CMC solution and nitrogen-XG solution in A 0.8 mm X 0.8 mm square capillary tube in a horizontal position - Sudarja Sudarja; Deendarlianto Deendarlianto; Sukamta Sukamta; Rahmad Kuncoro Adi; Fitroh Anugrah Kusuma Yudha; Rafil Arizona (Universitas Muhammadiyah Magelang, 2025)
Two-phase gas–liquid flow in small channels is important in mini/micro heat exchangers, flow chemistry and hydrogen transport subsystems (such as fuel cell manifolds and electrolysers), which require control of pressure loss and stable regimes. However, there is still a limited database of combinations of nitrogen gas and non-Newtonian fluids in square capillary pipes, even though shear-thinning properties can shift the transition map and increase sensitivity to superficial velocity. This study aims to address this issue by experimentally characterizing pressure gradients and flow patterns. Methods include testing nitrogen–polymer solutions in horizontal 0.8 × 0.8 mm square capillary tubes. The test fluids are carboxymethyl cellulose (CMC) and xanthan gum (XG), at concentrations of 0.2% and 0.4% by mass. The operating range included gas superficial velocity (JG) of 0.3–7.8 m/s and liquid superficial velocity (JL) of 0.03–1 m/s. The pressure gradient (Δp/L) was measured differentially, while the interface configuration was recorded for regime identification and flow pattern mapping. The results show that JL primarily controls the base level of Δp/L, while JG triggers a further increase once the transition threshold has been passed. Increasing the concentration from 0.2% to 0.4% raised Δp/L in all JG–JL combinations and advanced the transition. XG exhibited stronger shear thinning than CMC, resulting in a generally lower Δp/L, narrower churn regions and a more gradual transition from slug to annular flow. Flow pattern maps confirm the presence of a bubbly/plug domain at low JG, churn at medium and high JG–JL combinations, and annular flow at low JL and high JG. These findings provide an operating window to avoid churn and direct the system towards either stable bubbly/plug or stable annular flow. This is highly relevant for designing low- to medium-pressure hydrogen transport systems in small channels.